2014
DOI: 10.5303/jkas.2014.47.3.115
|View full text |Cite
|
Sign up to set email alerts
|

NVST Data Archiving System Based on Fastbit Nosql Database

Abstract: The New Vacuum Solar Telescope (NVST) is a 1-meter vacuum solar telescope that aims to observe the fine structures of active regions on the Sun. The main tasks of the NVST are high resolution imaging and spectral observations, including the measurements of the solar magnetic field. The NVST has been collecting more than 20 million FITS files since it began routine observations in 2012 and produces a maximum observational records of 120 thousand files in a day. Given the large amount of files, the effective arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Due to query-intensive nature of our experiments, this kind of indexing helps improve query performance. Liu et al (2014) reported good performance in index creation, query and storage space of this algorithm by comparing with a typical relational database (e.g., MySQL or PostgreSQL). The reader is referred to Liu et al (2014) for details of quantitative comparison between both database systems using high-resolution solar observations.…”
Section: Appendix 1 Database Systemmentioning
confidence: 92%
“…Due to query-intensive nature of our experiments, this kind of indexing helps improve query performance. Liu et al (2014) reported good performance in index creation, query and storage space of this algorithm by comparing with a typical relational database (e.g., MySQL or PostgreSQL). The reader is referred to Liu et al (2014) for details of quantitative comparison between both database systems using high-resolution solar observations.…”
Section: Appendix 1 Database Systemmentioning
confidence: 92%
“…At the end of the run, the DAQ updates this document with information such as the length of the run and the number of data files created. A full export of the DAQ settings at the start and at the end of the run is also attached to the run document 5 .…”
Section: Daq Integrationmentioning
confidence: 99%
“…The scale and the duration of the projects makes database approaches necessary for managing information about the detector components and the datasets. Projects have, for example, taken a database approach to managing the quality of detector components and their status [1,2,3], and to keeping track of datasets [4,5] and detector conditions [6]. In this work, we present a unified database approach to keeping track of detector hardware, response parameters, environment information, and datasets for the DEAP-3600 Dark Matter detector [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It utilizes a compressed bitmap index, encoding, and binning (Wu 2005;Wu et al 2009). A new data archiving system for the NVST based on the Fastbit NoSQL database has been implemented, where the average number of records generated by NVST in one year is approximately 10 to 12 million (Liu et al 2014). A Distributed Data Storage System (DDSS) for real-time observational data storage based on the Lustre distributed file system was implemented on the NVST (Liu et al 2015).…”
Section: Related Workmentioning
confidence: 99%